Tracheostomy care quality improvement in low- and middle-income countries: A scoping review. - Msiba Selekwa; Ivy Maina; Tiffany Yeh; Aslam Nkya; Isaie Ncogoza; Roger C Nuss; Beatrice P Mushi; Sumaiya Haddadi; Katherine Van Loon; Elia Mbaga; Willybroad Massawe; David W Roberson; et al. (PLOS Global Public Health)
Tracheostomy is a lifesaving, essential procedure performed for airway obstruction in the case of head and neck cancers, prolonged ventilator use, and for long-term pulmonary care. While successful quality improvement interventions in high-income countries such as through the Global Tracheostomy Collaborative significantly reduced length of hospital stay and decreased levels of anxiety among patients, limited literature exists regarding tracheostomy care and practices in low and middle-income countries (LMIC), where most of the world resides. Given limited literature, this scoping review aims to summarize published tracheostomy studies in LMICs and highlight areas in need of quality improvement and clinical research efforts. Based on the PRISMA guidelines, a scoping review of the literature was performed through MEDLINE/PubMed and Embase using terms related to tracheostomy, educational and quality improvement interventions, and LMICs. Publications from 2000-2022 in English were included. Eighteen publications representing 10 countries were included in the final analysis. Seven studies described baseline needs assessments, 3 development of training programs for caregivers, 6 trialed home-based or hospital-based interventions, and finally 2 articles discussed development of standardized protocols. Overall, studies highlighted the unique challenges to tracheostomy care in LMICs including language, literacy barriers, resource availability (running water and electricity in patient homes), and health system access (financial costs of travel and follow-up). There is currently limited published literature on tracheostomy quality improvement and care in LMICs. Opportunities to improve quality of care include increased efforts to measure complications and outcomes, implementing evidence-based interventions tailored to LMIC settings, and using an implementation science framework to study tracheostomy care in LMICs.